2016
DOI: 10.3329/jsr.v8i2.26511
|View full text |Cite
|
Sign up to set email alerts
|

Chemotaxis of Biofilm Producing <i>Pseudomonas</i> spp. towards Refined Petroleum Oil

Abstract: The bioavailability of organic contaminants to the degrading bacteria is a major limitation to efficient bioremediation of sites contaminated with hydrophobic pollutants. Studies were conducted to analyze the presence of biodegrading bacteria on the sites of refinery and garage oil spills with abundance of hydrocarbons. Contaminated soils were collected from these rich hydrocarbon sites and bacteria were isolated from samples using regular bacterial media enriched with petroleum oil. These isolates were charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…isolated from oil spillage site was found to exhibit chemotaxis towards hydrocarbons and had high in vitro degradation efficiency of 87.54% and 85.48% of diesel and kerosene respectively [80]. Similarly, in another study, the organism most efficient in degrading refined petroleum oil was found to be chemotactic, could form biofilm and was identified to be Pseudomonas aeruginosa [81]. Desai et al (2018) used rising oil droplets with dissolved chemoeffector to study the nutrient uptake efficiency of bacteria chemotactic to the compound.…”
Section: ) Hydrocarbonsmentioning
confidence: 88%
“…isolated from oil spillage site was found to exhibit chemotaxis towards hydrocarbons and had high in vitro degradation efficiency of 87.54% and 85.48% of diesel and kerosene respectively [80]. Similarly, in another study, the organism most efficient in degrading refined petroleum oil was found to be chemotactic, could form biofilm and was identified to be Pseudomonas aeruginosa [81]. Desai et al (2018) used rising oil droplets with dissolved chemoeffector to study the nutrient uptake efficiency of bacteria chemotactic to the compound.…”
Section: ) Hydrocarbonsmentioning
confidence: 88%